Squamous cell carcinoma of the nasal cavity: A descriptive analysis of cases from the head and neck 5000 study. (12th September 2019) - Dale, Oliver T.; Pring, Miranda; Davies, Amy; Leary, Sam; Ingarfield, Kate; Toms, Stu; Waterboer, Tim; Pawlita, Michael; Ness, Andy R.; Thomas, Steve J.
Abstract: Objectives: This paper aims to provide contemporary epidemiological data on squamous cell carcinoma (SCC) of the nasal cavity, which represents a rare type of head and neck cancer. Design, Setting & Participants: A descriptive analysis of people with nasal cavity SCC treated with curative intent from the Head and Neck 5000 study; a multicentre clinical cohort study of people from the UK with head and neck cancer. People with tumours of the nasopharynx, paranasal sinuses and other sub‐sites of the head and neck were excluded. Main outcome measures: Demographic data and treatment details are presented for all participants. The main outcomes were overall survival and survival according to categories of characteristics (eg, smoker vs non‐smoker); these were explored using Kaplan‐Meier plots. Results: Thirty people with nasal cavity SCC were included in the study, of which most were male (67%) and current or ex‐smokers (70%). The majority (70%) presented with early‐stage (T1/2, N0) tumours. Cervical lymph node metastases at presentation were rare, occurring in only one person. Nine people died during the follow‐up period (30%). Worse survival outcomes were seen in people with moderate or severe co‐morbidities. Conclusions: This paper provides epidemiological data on nasal cavity SCC in the UK. Patterns of disease and survival outcomes are described, identifying high‐risk groups. Further studies should explore whether primary treatment modality alters survival.